THE INFLUENCE OF WORKER STATUS, COMPETENCE AND WORK CULTURE ON EMPLOYEE PERFORMANCE PT SUMMIT OTO FINANCE SURABAYA - Ronggot, Marianus; Jannah S, Miftahul (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study aims to determine whether the variables of worker status (X1), employee competence (X2) and organizational culture (X3) simultaneously have a significant effect on employee performance (Y) PT Summit Oto Finance Surabaya.Data collection techniques are carried out through questionnaires, inter-views, and observation techniques, which consist of primary data and secondary data. Furthermore, the data was analyzed quantitatively, namely by using a statistical model in the SPSS 22.00 program, with descriptive analysis techniques and multiple linear regression analysis. The results showed that: There is a joint (simultaneous) influence of independent variables (X) in the form of worker status (X1), compe-tence (X2) and organizational culture (X3) on the dependent variable (Y), namely employee performance at the warehouse of PT Summit Oto Finance Surabaya, Based on the results of the t test calculations car-ried out, it can be seen that the independent variables (X) in the form of worker status (X1), competence (X2) and organizational culture (X3) partially have a significant effect on the dependent variable (Y), namely employee performance at the warehouse of PT Summit Oto Finance Surabaya.